KARAKTERISTIK AKUIFER DI KAWASAN PROSPEK BIJIH BESI PESISIR DESA KARANGTAWANG KECAMATAN NUSAWUNGU KABUPATEN CILACAP BERDASARKAN DATA RESISTIVITAS-2D - Sehah, Muhammad; Raharjo, Sukmahaji Anom; Vickramdani, Muhammad (Bulletin of Scientific Contribution, 2018)
The research to investigate the characteristic of aquifer using the 2D-geoelectrical resistivity method has been done in the iron ore prospect area of Nusawungu West Coastal, Cilacap Regency. The background of the research is the abundant potential of iron sand in this village which prospects are exploited. The 2D-resistivity data acquisition was carried out in March – April 2018 in four locations determined based on the prospect zone of iron ore from the local magnetic anomaly map of the research area. Based on the results of modeling and interpreting resistivity data, the potential of iron ore in the research area is quite large. In each trajectory of measurement, sand was found which was interpreted to contain iron ore with resistivity values ranging from 21.7 – 56.7 Ωm. The sand containing iron ore is also the main medium of the shallow groundwater aquifer layer in the research area. The characteristics of aquifers in the research area are quite good where the condition of the residents' well water is abundant, does not taste salty, has never experienced drought even during the dry season, but is thought to contain iron (Fe). If the exploitation of iron sand is carried out on a large scale, it will result in reduced sand and other rocks making up aquifers. As a result the function of aquifers in storing and flowing groundwater in the research area has decreased.